Determinants of Dietary Patterns and Obesity among Secondary School Adolescents in Harare, Zimbabwe, 2016 - Chapoterera, Byron; Maradzika, J. Chideme; Marume, Anesu; Zikiti, Admire (International Journal of Child Health and Nutrition, 2017)
Background: The dietary patterns are becoming a major public health concern. The current data from various studies in Zimbabwe shows that there was an increase in the prevalence of obesity among secondary school adolescents in Harare. There is a link between eating habits and obesity. This study was conducted to explore the factors influencing dietary practices among adolescents in Zimbabwean schools. Methods: A school based analytic cross sectional study was conducted with 283 pupils aged 13-19 years. Systematic random sampling was used. Data was collected using self-administered questionnaire based on the ecological framework. The aim of the study was to identify the relationship between dietary patterns and occurrence of obesity. Bivariate and multivariate logistic regression analysis was used to identify the relationship between dietary patterns and obesity. Findings: The prevalence of obesity was 11.4%. Females were 6.79 (95% CI: 2.17-21.22 p=0.001) more likely to be obese. Consumption of sugar and sweetened beverages were associated with occurrence of obesity; beverages (AOR=3.62, 95%CI=1.99-10.91 p=0.025); eating of snacks in between meals (AOR=2.40, 95%CI=1.03-5.64 p=0.004); so was being located in high density suburb (0R=0.45, 95CI=0.21-0.99 p=0.023); consuming burgers (OR=4.41, CI=1.54-12.64 p=0.006); being a pupil in lower adolescent with age less than 16 (OR=1.99 95%CI=0.99-4.27 p=0.038). Consuming a special diet that is recommended or as a choice was protective from obesity though this was not statistically significant. Not removing visible fat from meat was a risk factor for developing obesity. Eating the traditional maize meal staple food, sadza was protective to being obese (OR=0.3514, 0.16-0.78) Conclusions: The study showed that obesity is a cause for concern among school children as seen by 11.4% prevalence. Choice of meals is done by parents, eating a home cooked meal such as sadza, participating in meal planning was found to be reinforcing factors. There is need to create awareness on students, parents, teachers and the wider community to increase the adoption of healthy dietary practice among school children.